Sharia Banking Position in the Economic and the National Legal System - Sisca Debyola Widuhung; Aris Machmud (International Journal of Social Service and Research, 2022)
The Position of Sharia banking in Indonesia legal system is important. The study aims to find out how is the position of sharia banking in the national legal system. The method used in this research is normative juridical with qualitative analysis approach. Moreover, the result is the position of Islamic banks in the economic system is as a bank institution that helps the Indonesian economy in increasing financial inclusion and becomes an institution that carries out an intermediary function. In relation to the national legal system, Islamic banking has a strong position, because it is an inseparable part of the legal system in force in Indonesia.